Becoming a teenager in children infected through HIV vertical transmission: implications of nursing care - Thaís Silva de Souza; Ivone Evangelista Cabral; Cristiane Cardoso de Paula (Universidade Federal de Santa Maria, 2011)
Objective: to describe social and health demands of children who has HIV/AIDS through vertical transmission on the transition from childhood to adolescence. Method: qualitative research with descriptive approach, approved by Ethics Committee (096/06-EEAN/UFRJ; 09/07-IPPMG/UFRJ; 36/07-HUGG/UNIRIO). Information was obtained through interview with 11 children, aged between 12-14 years old, that knew their diagnosis. It was developed thematic content analysis. Results: social demands of becoming a teenager were identified: relationships, activities, scholar acquaintanceship, dating; and ill health demands: disclosure, hospital follow-up, medical treatment, prejudice, future. Conclusion: Face becoming a teenager, Erikson's psycho-social development theory, is coherent to social demands, but it doesn't address these children's special health needs. Health care needs to include children and their families monitoring during the pubertal development and the disease process